Emerging Energy Harvesting Materials and Devices for Self‐Powered Water Disinfection. Issue 7 (6th June 2021) - Huo, Zheng‐Yang; Lee, Dong‐Min; Wang, Si; Kim, Young‐Jun; Kim, Sang‐Woo
Abstract: Contaminated drinking water is one of the main pathogen transmission pathways making waterborne illnesses such as diarrheal diseases and gastroenteritis a huge threat to public health, especially in the areas where sanitation facilities and gird power are inadequate such as rural and disaster hit areas. Self‐powered water disinfection systems are a promising solution in these cases. In this review paper, the authors provide an overview of the new and emerging methods of applying energy harvesting materials and devices as a source of power for water disinfection systems microbial disinfection in water by harnessing ambient forms of energy such as mechanical motion, light, and heat into electricity. The authors begin with a brief introduction of the different energy harvesting technologies commonly applied in water disinfection; triboelectric, piezoelectric, pyroelectric, and photovoltaic effects. Various microbial disinfection mechanisms and types of device construction are summarized. Then, a detailed discussion of the energy harvester‐driven water disinfection process is provided. Finally, challenges and perspectives regarding the future development of self‐powered water disinfection are described. Abstract : Recent studies of energy harvesters to drive self‐powered water disinfection processes based on triboelectric, piezoelectric, pyroelectric, and photovoltaic effects are reviewed. Disinfection mechanisms and device layouts are summarized, and a detailed discussion of the energy harvester‐driven water disinfection process is provided. These self‐powered water disinfection systems can supply safe drinking water to rural and disaster‐stricken areas lacking reliable power supplies.